Disrupting the cinnamyl alcohol dehydrogenase 1 gene (BdCAD1) leads to altered lignification and improved saccharification in Brachypodium distachyon. (10th December 2012) - Bouvier d'Yvoire, Madeleine; Bouchabke‐Coussa, Oumaya; Voorend, Wannes; Antelme, Sébastien; Cézard, Laurent; Legée, Frédéric; Lebris, Philippe; Legay, Sylvain; Whitehead, Caragh; McQueen‐Mason, Simon J.; Gomez, Leonardo D.; Jouanin, Lise; et al.
Summary Brachypodium distachyon (Brachypodium) has been proposed as a model for grasses, but there is limited knowledge regarding its lignins and no data on lignin‐related mutants. The cinnamyl alcohol dehydrogenase (CAD) genes involved in lignification are promising targets to improve the cellulose‐to‐ethanol conversion process. Down‐regulation of CAD often induces a reddish coloration of lignified tissues. Based on this observation, we screened a chemically induced population of Brachypodium mutants (Bd21–3 background) for red culm coloration. We identified two mutants (Bd4179 and Bd7591), with mutations in the BdCAD1 gene. The mature stems of these mutants displayed reduced CAD activity and lower lignin content. Their lignins were enriched in 8–O–4‐ and 4–O–5‐coupled sinapaldehyde units, as well as resistant inter‐unit bonds and free phenolic groups. By contrast, there was no increase in coniferaldehyde end groups. Moreover, the amount of sinapic acid ester‐linked to cell walls was measured for the first time in a lignin‐related CAD grass mutant. Functional complementation of the Bd4179 mutant with the wild‐type BdCAD1 allele restored the wild‐type phenotype and lignification. Saccharification assays revealed that Bd4179 and Bd7591 lines were more susceptible to enzymatic hydrolysis than wild‐type plants. Here, we have demonstrated that BdCAD1 is involved in lignification of Brachypodium. We have shown that a single nucleotide change in BdCAD1 reduces the lignin level and increases the degree of branching of lignins through incorporation of sinapaldehyde. These changes make saccharification of cells walls pre‐treated with alkaline easier without compromising plant growth.